Provincial Oversight and University Autonomy in Canada: Findings of a Comparative Study of Canadian University Governance - Eastman, Julia Antonia; Jones, Glen Alan; Begin-Caouette, Olivier; Li, Sharon X; Noumi, Christian; Trottier, Claude (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
In order to fulfill their missions, research universities must maintain conditions and capacity for knowledge production and dissemination, while responding to the expectations of governments, other stakeholders, and/or markets. That universities succeed in this quest is vital, not only for their own future as organizations but also for the benefit of current and future generations of students, stakeholders, and society at large. We sought to contribute to the understanding of how higher education institutions and systems rise to the challenge of achieving and sustaining relative institutional autonomy by conducting a comparative case study of the governance of six major universities in five provinces in Canada. This article presents our findings with respect to provincial oversight of the case universities. We found that the case universities appeared to be coming from and to remain at different points on a state supervision/autonomy continuum, but all appeared to be experiencing greater provincial supervision.